Efektivitas Pemberdayaan Masyarakat Melalui Badan Usaha Milik Desa Di Desa Tawa –Tawaro Kecamatan Tinondo Kabupaten Kolaka Timur - Meitasya, Aisya; Qomariyah, Erni; Darpin, Darpin (REZ PUBLICA, 2021)
This study aims to determine the effectiveness of community empowerment through Village-Owned Enterprises (BUMDes) in Tawa-Tawaro Village, Tinondo District, East Kolaka Regency. Tinondo District, East Kolaka Regency. The method used in this study is a qualitative descriptive research method by means of observation, interviews and documentation. The results of this study indicate that for community empowerment based on research conducted, it can be seen that the effectiveness of community empowerment has progressed in terms of good management. carried out by Bumdes in Tawa Tawaro Village, Tinondo District, East Kolaka Regency. On the aspect of progress in community empowerment carried out by Bumdes in Tawa Tawaro village, the community, which consists mostly of farmers, can l It is easier to get fertilizers and plant poisons that they need in their daily activities and activities. The Bumdes management is done independently and in the process of implementation, the community in getting the materials they need at the Tawa Tawaro Bumdes they can take the materials to be paid later and things This is a form of convenience provided to the community in managing Bumdes in Tawa Tawaro Village.